2003
DOI: 10.1177/09680519030090060901
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for endotoxic and antagonistic activities: investigation with novel synthetic lipid A analogs

Abstract: Our early work using homogeneous synthetic preparations demonstrated the presence of a lipid A analog which antagonizes endotoxic activities of LPS and lipid A. The first example was a tetraacylated biosynthetic precursor, now known as precursor Ia or lipid IVa, that contains four 3-hydroxytetradecanoyl moieties linked to the bisphosphorylated disaccharide backbone common to the endotoxic hexa-acyl Escherichia coli lipid A. Various compounds with both endotoxic and antagonistic activities have subsequently bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…Lipid A structure and configuration of endotoxin are known to determine the agonist or antagonist activity (24,27,37). For example, the KDO 2 -lipid A structure of meningococcal lipooligosaccharide (LOS) is necessary for the maximal agonist activation of macrophages via the TLR4 complex (51).…”
mentioning
confidence: 99%
“…Lipid A structure and configuration of endotoxin are known to determine the agonist or antagonist activity (24,27,37). For example, the KDO 2 -lipid A structure of meningococcal lipooligosaccharide (LOS) is necessary for the maximal agonist activation of macrophages via the TLR4 complex (51).…”
mentioning
confidence: 99%
“…Schromm et al (34) found that the number, nature, and location of negatively charged molecules modulate the molecular conformation of E. coli LPS and lipid A and are linked to IL-6 inducing capacity. Recently, synthetic lipid A with two KDO molecules was found to have enhanced agonist activity compared to one KDO molecule or none (18,50). A decreased number or lack of KDO and hydroxymyristic acid is proposed as a contributor to low endotoxic activity of Leptospira interrogans (46), Francisella tularensis (47), Legionella pneumophila, and different Rhizobium species LPSs (32,51).…”
Section: Vol 72 2004mentioning
confidence: 99%
“…Lipid A moieties that deviate from this pattern often demonstrate a significant low endotoxic activity [Alexander and Rietschel, 2001]. For example, lipid A molecules with penta-or hepta-acyl chains are ∼ 100 times less active, while lipid A with tetra-acyl chains lacks agonistic activity altogether and acts as an antagonist instead [Hajjar et al, 2002;Kusumoto et al, 2003]. In this study, our data revealed that the whole cells, OMVs and purified LPS under PagL expression lessened toxicity.…”
Section: Discussionmentioning
confidence: 57%
“…The structure-function analysis of lipid A signaling indicates that the length and number of acyl side chains are critical for TLR4 signaling [Hajjar et al, 2002;Kusumoto et al, 2003]. Optimal lipid A potency is achieved by a biphosphorylated, hexa-acylated lipid A species that has acyl chains 12-14 carbons in length [Raetz and Whitfield, 2002].…”
Section: Discussionmentioning
confidence: 99%